New species of Cinygmula McDunnough, 1933 and larval description of Cinygmula irina Tshernova & Belov, 1982 from the Russian Far East (Ephemeroptera: Heptageniidae) - Tiunova, Tatiana M.; Gorovaya, Ekaterina A. (Zootaxa, 2013)
Here, we describe Cinygmula tetramera, sp. nov. (Ephemeroptera: Heptageniidae), which has male imaginal forceps with three distal segments, based on male & female imagos reared from larvae. The structure of the penes of this species is similar to that of Cinygmula irina Tshernova & Belov, 1982, a description and drawing of which are also presented in this paper. The larvae of C. irina are described for the first time. We also describe the eggs of both species. Based on our data, egg characters provide useful data for species diagnoses in the genus Cinygmula.